Disturbance observer‐based distributed sliding mode control of multimotor web‐winding systems. Issue 4 (7th January 2020) - Nian, Xiaohong; Fu, Xinran; Chu, Xiaoyan; Xiong, Hongyun; Wang, Haibo
Abstract : This study investigates a novel disturbance observer‐based distributed sliding mode control (DOB‐DSMC) strategy for the multimotor web‐winding system in the presence of model uncertainties and external disturbances. First, a disturbance observer is developed for each subsystem to generate the disturbance estimations, which can be incorporated in the controller to counteract the disturbances. After that, by choosing appropriate coordination variables, a DOB‐DSMC is designed, which ensures that the system states converge to the sliding surface in finite time. The proposed controller can not only reduce the effect of coupling between continuous subsystems on states but also restrain the influence of uncertainties and external disturbances. It only requires a smaller control input than linear control. The controller gain matrices are obtained by solving linear matrix inequalities, which are obtained by the H ∞ control theory and Lyapunov stability theory. Finally, some simulations and experimental tests are performed on the three‐motor web‐winding system to test the performance of the proposed DOB‐DSMC method.